Pelatihan Microsoft Office PowerPoint Sebagai Bahan Ajar Bagi Guru SMPN 18 Kota Bengkulu - Marhalim; Andilala; Khairullah (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2022)
The use of media in the learning process is very important to facilitate students' understanding of the learning materials. The media will facilitate the interaction of teachers with students so that it is expected to optimize the learning process. The benefits that can be obtained from the use of learning media include: The delivery of learning materials can be uniformed, the learning process can be more interesting, the learning process becomes more interactive, the amount of teaching and learning time can be reduced. The training program for making learning media by teachers of SMPN 18 Bengkulu City aims to: How to improve the ability of SMPN 18 Bengkulu City teachers in developing their own learning media, What efforts need to be made so that the ability to develop learning media for SMPN 18 City teachers Bengkulu. The results or conclusions: There is a suitability of the material with the needs of the teachers of SMP N 18 Bengkulu City, There is a positive response from the participants, Most (85%) participants have understood the importance of learning media in improving the quality of learning, and have skills in making media Power point.